Description of the Bolsa Família-Habitação relationship based on the national household sampling survey - Continuous for the 1st visit of the year 2022× - Sousa, Jorge Alves de; Santos, Verônica Dantas dos (Seven Editora, 2024)
This article describes, through a statistical analysis, the relationship between the Federal Government's Bolsa Família (BF) Program and the housing situation of those contemplated in the Program, based on the Continuous National Household Sample Survey - Continuous PNAD, 1st Visit for the year 2022. For this analysis, the microdata collected based on the questionnaire used in the research were consulted, as well as technical notes made available by the Brazilian Institute of Geography and Statistics (IBGE). Because it is a reliable source for obtaining statistical information on the demographic, social, economic and housing characteristics of the Brazilian population, and using quantitative methodology, the data were analyzed using the R software and the survey package. The results obtained through this statistical analysis showed that there is a significant number of low-income people who own their own homes; the value of the rent is extremely expensive, in most of the FUs, especially in the South, Southeast and Midwest regions of the country, which compromise more than 100% of the amount received by the BF. We can see that BF has a relationship with housing, considering that the amount received by the beneficiaries minimizes housing inequality, since this value helps families with essential costs for survival. In this sense, more studies are needed to help in the understanding of the conditions in which these dwellings are found, in order to promote and improve public policies aimed at housing in order to improve the living conditions of the low-income population. DOI:https://doi.org/10.56238/sevened2024.014-004